Basket‐weave structure in the stratum corneum is an important factor for maintaining the physiological properties of human skin as studied using reconstructed human epidermis and tape stripping of human cheek skin. (25th August 2019) - Goto, H.; Tada, A.; Ibe, A.; Kitajima, Y.
Summary: Background: The normal stratum corneum (SC) has an upper basket‐weave (BW) pattern layer and a lower compact layer. The transition from compact to BW SC is well associated with a transition from diffuse to peripheral distributions of corneodesmosomes (CDs). The loss of transition from compact SC to BW SC appears to cause structural and barrier‐function impairments. Objectives: To show the involvement of the BW SC in maintaining the physiological properties of the skin. Methods: Reconstructed human epidermis (RHE) with a complete BW structure was created by treatment with prepared emulsion‐A, an oil‐in‐water emulsion. The RHE tissues were subjected to histological analysis, and the distribution of CDs on the SC with or without BW SC was analysed by anti‐desmoglein (Dsg)1 antibody immunofluorescence and ultrastructural and Western blotting analyses. Ultrastructural analysis of intercellular lipids was performed. The mechanical properties of the RHE were evaluated. Results: Emulsion‐A successfully generated the BW SC in the RHE in which the degradation of CDs was promoted. The intercellular space of the BW SC generated by emulsion‐A was filled with multilamellar lipid sheets. The softness of the SC with a BW structure formed with emulsion‐A was higher than that of the compact SC in RHE. The outermost SC Dsg1 degradation (formation of the BW SC as determined with Dsg1 pixels) was correlated with water‐barrier functions and the SC softness of healthy human cheek, which varied widely. Conclusions: Emulsion‐A successfully generated the BW SC in RHE for the first time. This method is suggested to be a useful tool for investigating the physiological significance of the BW SC in vitro . Determination of Dsg1 content in the SC obtained by tape stripping from human skin allows study of the effects of external stimulants, such as creams and ointments, including cosmetics, on the completeness of the BW SC in situ without biopsy. What's already known about this topic? The normal stratum corneum (SC) has two layers, an upper basket‐weave (BW) pattern layer and a lower compact layer. Epidermal diseases such as ichthyosis vulgaris and X‐linked ichthyosis have an incomplete or no BW SC and impaired SC barrier functions, in which corneodesmosome (CD) degradation in a peripheral distribution is impaired. The roles of the BW SC in the physiological properties of human skin have not been clearly elucidated. What does this study add? Reconstructed human epidermis (RHE) with a complete BW structure was generated for the first time by treatment with oil‐in‐water emulsion‐A. The formation of the BW SC was associated with a decrease in Dsg1 content, which represents the CD number in the SC. The intercellular space of the BW SC generated by emulsion‐A, but not compact SC, was filled with multilamellar lipid sheets. The softness of the SC with a BW structure formed by emulsion‐A treatment was higher than that of the compact SC in RHE. What is the translational message? RHE with a complete BW SC generated by emulsion‐A treatment is suggested to be a useful tool for investigating effects on the physiological functions of the BW SC, as in treatments with creams and ointments including cosmetics. Determination of desmoglein 1 content in the SC obtained by tape stripping from human skin can make it possible to study the effects of external stimulants, such as creams and ointments, including cosmetics, on the completeness of the BW SC in situ without biopsy. Abstract : Linked Comment:  Ishida‐Yamamoto. Br J Dermatol 2020; 182 :269–270 . Plain language summary available online Respond to this article